Living with acute coronary syndrome and prediabetes : an interpretive description of complex illness : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Nursing at Massey University, Wellington, New Zealand - Van Wissen, Kim (Massey University, 2013)
The purpose of this research is to reveal the experience and interpretation people have of cardiovascular disease (CVD) and prediabetes as complex illness. CVD and diabetes are both increasing in prevalence in New Zealand and globally. Prediabetes is known to be precursory to type 2 diabetes; CVD and prediabetes are fast becoming an established comorbidity. As the prevalence of complex illness soars, the experience and interpretation people have of their condition requires deeper appreciation by nurses as members of a practice discipline. This doctoral research draws attention to the experiences as interpreted by participants and subsequently by the researcher, using interpretive description informed by Gadamer and Merleau-Ponty. Thirty three participants with CVD and prediabetes were recruited into this study. Open ended interviews were undertaken in hospital before discharge and then approximately 9 months later in the community. Interviews were transcribed, data managed by NVivo 9 software, data analysed using thematic analysis, and a thematic framework was developed to organise themes. The overarching theme is in/conspicuous detail indicating the visible and the invisible elements of complex illness. The two major themes, invisible disequilibrium and dialogue as caring, foreground further subthemes and embedded subthemes. The major theme invisible disequilibrium describes the experience of illness and is supported by three subthemes: losing equilibrium, becoming embattled and making sense of evolving illness. The second major theme dialogue as caring interprets the experiences participants had and is supported by subthemes: restorative dialogue, caring and constructing illness. Major findings indicate that complex illness is heterogeneous and participants were continually working with and making sense of the conspicuous and less conspicuous detail of ‘the whole’. Further findings include the proclivity of risk (choice) as a function of participants’ lifestyle such as diet type, activity levels, understanding of medications, plus how this risk may in the longer term cause disease and illness. A third major finding is that participants focussed on self-care as part of their construction of illness. This research provided insights into the experiences of people with CVD and prediabetes. It also showed that complex illness is the occurrence of an intricate meshing of personal circumstances, signs and symptoms that requires attending to needs as identified by the patient. This continues the debate concerning how illness affects the lives of individuals, potentially influencing future service planning.
Keywords: Coronary heart disease; Prediabetic state; Patients